S3: Storable, Shareable Search - Morris, Meredith Ringel; Horvitz, Eric (Proceedings of Interact 2007, 2007)
We present S3, a system that implicitly captures the process and products of Web investigations (exploratory searches involving multiple queries). This automatically-created, persistent representation of an investigation enables future review and continuation of suspended search activities. This persistent representation can reduce unnecessary re-execution of queries and enable users to quickly regain the context of a resumed activity. Stored investigations can also be shared with, and augmented by, collaborators. Furthermore, a stored investigation can act as a standing query, proactively updating itself when a user revisits it.